Relative Effectiveness of Selected Extension Teaching Methods for Imparting Knowledge about Poplar Cultivation to the Farmers (Indian Journal of Extension Education, 2014)
The study was conducted in Gurdaspur and Hoshiarpur districts of Punjab among 120 poplar cultivators to assess the relative effectiveness of two extension teaching methods viz. lecture discussion and slides cum recorded messages. It was observed that mean knowledge gown score was more in the case of lecture discussion method (18.64) compared to slide cum recorded message method (15.25). It was also revealed that level of education and extension contact of farmer had positive and significant relationship with knowledge gain through the selected extension teaching method.